ARAHAN KEBIJAKAN PENGENDALIAN EROSI DAN SEDIMENTASI DI SUB DAERAH ALIRAN SUNGAI KEDUANG KABUPATEN WONOGIRI - Joko Sutrisno; Bunasor Sanim; Asep Saefuddin; Santun R.P. Sitorus (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : The Policy Direction for Controlling of Erosion and Sedimentation at Keduang Sub‐Watershed in Wonogiri Regency. Keduang Sub‐Watershed  is one of important sub‐watershed  at Bengawan Solo Watershed. Land  resources  management   at  Keduang  Sub‐Watershed   will  be  influence  of  environment quality,  physic (erosion,  sedimentation,  debit of Keduang  River),  chemistry  (water quality)  and socio economic aspect. This aim research to know the level of erosion and sedimentation  and to arrange  policy direction  for controlling  erosion and sedimentation  at Keduang  Sub‐Watershed, Wonogiri Regency.Research method which is used is descriptive. Data types which are obtained are secondarydata from Centre of Research and Development Technology of Watershed Management, Forestry Department,   BPS‐Statistic   of  Wonogiri   Regency   and   Agriculture   Department   of  Wonogiri Regency. Method of analysis’s data which is used in this research is Universal Soil Loss Equation (USLE)  Method  to predict  the soil erosion.  This research  method  also to arrange  modelling  of controlling erosion and sedimentation.Results   of  this   research   are:   the   level   of  erosion   in  Keduang   Sub‐Watershed   is  44 ton/ha/year   or  1.9  million  ton/year.   The  sediment   yield  from  Keduang   Sub‐Watershed   to Wonogiri  Basin  equal 164,000  ton/year.  Improving  of construction  terrace  can reduce  erosion and sedimentation.Keywords: land resources management, erosion, sedimentation, construction terrace